Changes in Maximal Strength and Home Run Performance in NCAA Division I Baseball Players Across 3 Competitive Seasons: A Descriptive Study - W. Guy Hornsby; Abigail L. Tice; Jason D. Stone; Justin J. Merrigan; Joshua Hagen; John P. Wagle; Aaron J. Cunanan; Michael H. Stone (Journal of Functional Morphology and Kinesiology, 2021)
The purpose of this longitudinal, descriptive study was to observe changes in maximal strength measured via isometric clean grip mid-thigh pull and home runs (total and home runs per game) across three years of training and three competitive seasons for four National Collegiate Athletic Association (NCAA) Division 1 baseball players. A one-way repeated measures analysis of variance (ANOVA) was performed, revealing significant univariate effects of time for peak force (PF) (p = 0.003) and peak force allometrically scaled (PFa) (p = 0.002). Increases in PF were noted from season 1 to season 2 (p = 0.031) and season 3 (p = 0.004), but season 2 was not significantly different than season 3 (p = 0.232). Additionally, increases in PFa were noted from season 1 to season 2 (p = 0.010) and season 3 (p < 0.001), but season 2 was not significantly different than season 3 (p = 0.052). Home runs per game rose from the 2009 (0.32) to 2010 season (1.35) and dropped during the 2011 season (1.07). A unique aspect of the study involves 2010 being the season in which ball-bat coefficient of restitution (BBCOR) bats were introduced to the NCAA competition.